Kesuksesan Sistem Cyber Extension dengan Pendekatan DeLone and McLean Information Systems Success Model di Kabupaten Wonogiri - Wydha Sari Hastyana Putri; Dwiningtyas Padmaningrum; Widiyanto Widiyanto (Universitas Sebelas Maret, 2022)
Cyber extension is a form of internet-based information system that expected to facilitate an access of information about the development of innovation in agriculture. This study aims to determine the relationship between variables which affect the success of the information system by DeLone and McLean in the information system of cyber extension in Wonogiri Regency. The basic method used is quantitative with survey techniques. The research location is in Wonogiri Regency. The sample was selected using a non-probability sampling technique with purposive sampling. The samples taken by 66 agricultural extension officers that include in 10 sub-district of Wonogiri Regency. Data collected by using questionnaires, interviews and documentation. Data analysis performed using structural equation modeling based on partial least square. The results of this study are the system quality has an effect on use, system quality has no effect on user satisfaction, information quality has no effect on use, information quality has an effect on user satisfaction, use has no effect on user satisfaction, user satisfaction has no effect on use, use has no effect on the individual impact and user satisfaction has an effect on the individual impact. The information quality on the cyber extension website is related to the success of the cyber extension system. The information quality will help increase the individual impact on the users of the cyber extension website.